2021
DOI: 10.1101/2021.03.29.437515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enrichment of SARS-CoV-2 entry factors and interacting intracellular genes in peripheral immune cells

Abstract: SARS-CoV-2 uses ACE2 and TMPRSS2 to gain entry into the cell. However, recent studies have shown that SARS-CoV-2 may use additional host factors that are required for the viral lifecycle. Here we used publicly available datasets, CoV associated genes and machine learning algorithms to explore the SARS-CoV-2 interaction landscape in different tissues. We find that in general a small fraction of cells expresses ACE2 in the different tissues including nasal, bronchi and lungs. We show that a small fraction of imm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…[27][28][29][30]32,33 There is additional evidence that retinoid signaling activation can effectively suppress coronaviruses. 34 Our docking study reveals that COVID-19 spike protein binds directly to the integral membrane receptor (STRA 6). STRA 6 mediates cellular uptake of retinol (Vitamin A) by recognizing a molecule of RBP-retinol to trigger release and internalization of retino.…”
Section: Introductionmentioning
confidence: 92%
“…[27][28][29][30]32,33 There is additional evidence that retinoid signaling activation can effectively suppress coronaviruses. 34 Our docking study reveals that COVID-19 spike protein binds directly to the integral membrane receptor (STRA 6). STRA 6 mediates cellular uptake of retinol (Vitamin A) by recognizing a molecule of RBP-retinol to trigger release and internalization of retino.…”
Section: Introductionmentioning
confidence: 92%
“…Interestingly, lymphocytes in alveoli, pancreas, oesophagus, and spleen did not express ACE2 gene. but a small fraction of T-cells in kidney , colon , heart and lung expressed ACE2 gene (34). It was found that the fraction of ACE2 expressing immune cells is very small (34).…”
Section: -Reducing Plasma Retinol and Inducing Circulating Rbp4mentioning
confidence: 99%
“…but a small fraction of T-cells in kidney , colon , heart and lung expressed ACE2 gene (34). It was found that the fraction of ACE2 expressing immune cells is very small (34). Another study investigated the expression of TMPRSS2 and ACE2 across databases of multiple single-cell sequencing including 9 independent studies.…”
Section: -Reducing Plasma Retinol and Inducing Circulating Rbp4mentioning
confidence: 99%
See 1 more Smart Citation